2004
DOI: 10.1165/rcmb.2003-0246oc
|View full text |Cite
|
Sign up to set email alerts
|

Role of Surfactant Protein-A in Nitric Oxide Production and Mycoplasma Killing in Congenic C57BL/6 Mice

Abstract: We generated congenic surfactant protein A (SP-A)-deficient (SP-A[-/-]) mice on the mycoplasma resistant C57BL/6 background (B6.SP-A[-/-]) and characterized their response to mycoplasma infection in comparison to C57BL/6 (B6) mice. B6.SP-A(-/-) mice infected with 10(6) colony-forming units (cfu) of Mycoplasma pulmonis had significantly higher bacterial lung loads than B6 mice at 72 h postinfection (p.i.). At the higher infection dose of 10(7), B6.SP-A(-/-) mice had significantly higher lung cfu at 24 h; howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 28 publications
1
30
1
1
Order By: Relevance
“…As a member of the collectin family of host defense proteins, SP-A also contributes to innate pulmonary immunity (11)(12)(13). We have previously studied M. pulmonis infection in B6 mice and showed that SP-A is necessary for maximal mycoplasma killing (4,14,15) by AM by upregulating the production of NO and reactive oxygen-nitrogen intermediates in these cells (14,15). Both SP-A Ϫ/Ϫ and iNOS Ϫ/Ϫ mice have a decreased ability to clear intratracheally instilled mycoplasmas.…”
Section: Clinical Relevancementioning
confidence: 99%
See 2 more Smart Citations
“…As a member of the collectin family of host defense proteins, SP-A also contributes to innate pulmonary immunity (11)(12)(13). We have previously studied M. pulmonis infection in B6 mice and showed that SP-A is necessary for maximal mycoplasma killing (4,14,15) by AM by upregulating the production of NO and reactive oxygen-nitrogen intermediates in these cells (14,15). Both SP-A Ϫ/Ϫ and iNOS Ϫ/Ϫ mice have a decreased ability to clear intratracheally instilled mycoplasmas.…”
Section: Clinical Relevancementioning
confidence: 99%
“…C57BL/6 SP-A Ϫ/Ϫ (B6.SP-A Ϫ/Ϫ ) N10 mice were generated from 129 ϫ BS SP-A Ϫ/Ϫ mice provided by Drs. Whitsett and Korfhagen (University of Cincinnati, Ohio) (16) by backcrossing for at least 10 generations onto the B6 background (15). Mice were bred at the University of Alabama at Birmingham (UAB), and genotype was characterized from tail DNA as described previously (15).…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Surfactant protein A (SP-A), a 34-to 36-kDa glycoprotein, plays a major role in the modulation of innate host defense in the lung (7,16,21,41,48,52). SP-A has been shown to stimulate chemotaxis of macrophages (70), enhance phagocytosis (11,34,44,46,47,50,63), induce generation of reactive oxidants (61), regulate the nitric oxide production (1,23), and influence the proliferation of immune cells (2,38) and the production of proinflammatory cytokines (3,27,37,39,68,69). SP-A can bind to receptors on the macrophage membrane (35).…”
mentioning
confidence: 99%
“…Показано, что SP-A воздействует на рост и жизнеспособность микроорга-низмов, повышая проницаемость микробной клеточной мембра-ны [3], регулирует механизмы иммунной защиты в легких путем связывания звеньев врожденного и приобретенного компонен-тов иммунитета [4], стимулирует хемотаксис макрофагов [5], вли-яет на пролиферацию клеток иммунного ответа и на продукцию провоспалительных цитокинов [6,7], повышает продукцию ре-активных оксидантов [8], регулирует продукцию оксида азота [9], стимулирует фагоцитоз [10][11][12].…”
unclassified